2019
DOI: 10.3390/mti3010019
|View full text |Cite
|
Sign up to set email alerts
|

Guidance in Cinematic Virtual Reality-Taxonomy, Research Status and Challenges

Abstract: In Cinematic Virtual Reality (CVR), the viewer of an omnidirectional movie can freely choose the viewing direction when watching a movie. Therefore, traditional techniques in filmmaking for guiding the viewers’ attention cannot be adapted directly to CVR. Practices such as panning or changing the frame are no longer defined by the filmmaker; rather it is the viewer who decides where to look. In some stories, it is necessary to show certain details to the viewer, which should not be missed. At the same time, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 107 publications
(91 reference statements)
1
39
0
3
Order By: Relevance
“…Researchers have suggested that visual overt cues, which are this paper's focus, differ in effectiveness for guiding attention based on their position within the user's FOV [66]. Posner [59] famously described attention as a spotlight, as it is narrow and directed at fixated objects in the center of gaze.…”
Section: Reacting To Central Versus Peripheral Cuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have suggested that visual overt cues, which are this paper's focus, differ in effectiveness for guiding attention based on their position within the user's FOV [66]. Posner [59] famously described attention as a spotlight, as it is narrow and directed at fixated objects in the center of gaze.…”
Section: Reacting To Central Versus Peripheral Cuesmentioning
confidence: 99%
“…Equally, some CVR-users are concerned about missing plot elements due to a lack of guidance [45,67]. In response to this, researchers have suggested that visual cues can be an effective way to guide users to Regions of Interest (ROIs) [66]. Popular techniques include stimulus-based luminance modulations * e-mail: anastasia.schmitz.18@alumni.ucl.ac.uk (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, instead of using a regular monitor, we conduct our experiments in an immersive VR setting. The reason for this is three-fold: First, VR offers a greater control over the conditions of the experiment, increasing reproducibility and repeatability; second, it allows for a more natural exploratory behavior of the subject, including walking around the scene, in contrast with previous approaches that required a fixed head position; and third, auditory-triggered visual performance degradation can find key applications in VR, where control of the user's attention is a fundamental challenge 20 . Moreover, it has been assumed in the literature that the visual performance degradation is caused by neural inhibitory interactions between the auditory and visual sensory pathways.…”
Section: Auditory Stimuli Degrade Visual Performance In Virtual Realimentioning
confidence: 99%
“…In CVR viewers see only a part of the omnidirectional movie on the display. Therefore, in some cases guiding methods are necessary so the viewer does not miss important details (Mateer 2017;Nielsen et al 2016;Rothe et al 2019). For this established filmmaking techniques can be used, for example sounds, lights and movements (Rothe and Hußmann 2018).…”
Section: Video Players For Omnidirectional Moviesmentioning
confidence: 99%